Kitice v odstavkih - Svetina, Peter (Slavistična revija, 2000)
In their effort to spread the new religious teachings, sixteenth-century Slovene Protestant writers published, among other things, several hymnals. With the tunes adapted from the hymnals by the German and Czech Protestants, they introduced into Slovene (spiritual) poetry numerous new stanza forms, four of which are discussed in the article.
Keywords: 16.st.; kitica; metrika; protestantizem; rima; slovenska književnost; slovenska poezija